Threats and sympathy for authoritarian candidates: evidence from Peru - Maldonado, Arturo (Revista Latinoamericana de Opinión Pública, 2020)
This article assesses whether the relationship between authoritarian predispositions and sympathy for authoritarian candidates is amplified in the presence of economic or security threats. The analysis is carried out on data from a national survey applied after the first round of the last presidential election of 2016 in Peru that included measures of sympathy for three candidates: Keiko Fujimori, perceived as authoritarian, and Pedro Pablo Kuczynski and Verónika Mendoza, considered non-authoritarian candidates. The instrument included a vignette experiment with news about the economy and crime, worded in such a way as to emphasize the threats about these issues. This survey also measured individuals’ authoritarianism through attitudes towards child rearing. Results indicate that in threatening situations, especially economic ones, the most authoritarian citizens more greatly value an authoritarian candidate like Keiko Fujimori. This effect is not detected for nonauthoritarian candidates competing in this election.